Pharmacological treatment in Parkinson's disease: Effects on gait. (October 2016) - Smulders, Katrijn; Dale, Marian L.; Carlson-Kuhta, Patricia; Nutt, John G.; Horak, Fay B.
Abstract: Gait impairments are a hallmark of Parkinson's disease (PD), both as early symptom and an important cause of disability later in the disease course. Although levodopa has been shown to improve gait speed and step length, the effect of dopamine replacement therapy on other aspects of gait is less well understood. In fact, falls are not reduced and some aspects of postural instability during gait are unresponsive to dopaminergic treatment. Moreover, many medications other than dopaminergic agents, can benefit or impair gait in people with PD. We review the effects of pharmacological interventions used in PD on gait, discriminating, whenever possible, among effects on four components of everyday mobility: straight walking, gait initiation, turning, gait adaptability. Additionally, we summarize the effects on freezing of gait. There is substantial evidence for improvement of spatial characteristics of simple, straight-ahead gait with levodopa and levodopa-enhancing drugs. Recent work suggests that drugs aiming to enhance the acetylcholine system might improve gait stability measures. There is a lack of well-designed studies to evaluate effects on more complex, but highly relevant walking abilities such as turning and making flexible adjustments to gait. Finally, paucity in the literature exists on detrimental effects of drugs used in PD that are known to worsen gait and postural stability in the elderly population. Highlights: Dopaminergic drugs improve spatial characteristics of straight-ahead gait. There is a lack of studies addressing other walking abilities, such as turning. Pro-cholinergic drugs might improve gait stability measures. There is a lack of studies evaluating drugs known to increase fall risk in elderly.